Tourette Syndrome and Driving. Issue 5 (5th May 2021) - Makhoul, Karim; Jankovic, Joseph
Abstract: Background: Driving ability may be impaired in patients with various movement disorders, but it has not been studied in patients with Tourette syndrome (TS). Cases: We describe a series of 6 patients from our large cohort of TS patients followed in our movement disorders clinic in whom severe tics have had interfered with their driving abilities. The motor tics involved facial muscles and caused visual impairment because of frequent blinking and transient blepharospasm (dystonic tic), but complex limb and truncal tics also seriously impacted their driving. Conclusions: Although majority of patients with TS have no functional impairment, severe motor tics in some patients may adversely affect their driving ability, potentially causing danger to themselves and others. Screening for such troublesome tics should be considered in patients with TS, particularly in teenagers who are being evaluated for driver's licensing.